2016
DOI: 10.3390/vaccines4040038
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Immune Regulatory Networks to Counteract Immune Suppression in Cancer

Abstract: The onset of cancer is unavoidably accompanied by suppression of antitumor immunity. This occurs through mechanisms ranging from the progressive accumulation of regulatory immune cells associated with chronic immune stimulation and inflammation, to the expression of immunosuppressive molecules. Some of them are being successfully exploited as therapeutic targets, with impressive clinical results achieved in patients, as in the case of immune checkpoint inhibitors. To limit immune attack, tumor cells exploit sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 110 publications
0
10
0
3
Order By: Relevance
“…Moreover, the depletion of host Tregs that are resistant to lymphodepletion results in the successful treatment of advanced tumor models when combined with lymphodepletion by cyclophosphamide and the transfer of naïve T cells [ 4 ]. Extensive studies have revealed that tumors induce immune suppression to evade antitumor T cell responses [ 13 15 ]. Several mechanisms have been suggested for the induction of immune suppression by tumors, including induction of Tregs, myeloid-derived suppressor cells, tumor-associated macrophages and tolerogenic DCs; secretion of immunosuppressive soluble factors; and activation of negative regulatory pathways such as CTLA-4 and PD-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the depletion of host Tregs that are resistant to lymphodepletion results in the successful treatment of advanced tumor models when combined with lymphodepletion by cyclophosphamide and the transfer of naïve T cells [ 4 ]. Extensive studies have revealed that tumors induce immune suppression to evade antitumor T cell responses [ 13 15 ]. Several mechanisms have been suggested for the induction of immune suppression by tumors, including induction of Tregs, myeloid-derived suppressor cells, tumor-associated macrophages and tolerogenic DCs; secretion of immunosuppressive soluble factors; and activation of negative regulatory pathways such as CTLA-4 and PD-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, TCR functions are impaired in tumor-bearing hosts [ 11 ] [ 12 ]. Tumor cells induce immunosuppressive mechanisms, such as the induction of regulatory cell populations and the secretion of immunosuppressive soluble factors, and they also inhibit the function of antitumor T cells [ 13 , 14 ] [ 15 ]. Thus, it remains difficult to harvest a sufficient number of fully functional naïve T cells from cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Залогом успешной терапии является понимание процессов, происходящих в опухолевом микроокружении, одним из определяющих факторов которого является уровень инфильтрации опухоли Т-клетками. Оценить Т-клеточную инфильтрацию возможно, исследовав уровень T-регуляторных лимфоцитов (Т-reg), а также связанных с опухолью макрофагов, сосудистых эндотелиальных клеток, фибробластов и иммуносупрессивных метаболитов, например кинуренина [61].…”
Section: таргетная терапия и исследования на уровне клеток клеточныхunclassified
“…Изучение Т-reg, которые являются одним из сильнейших иммуносупрессоров микроокружения, проводили с помощью МКАт и дендритноклеточных (ДК) вакцин. Клинические иссле-Черные -в разработке Красные -утверждены дования даклизумаба, сорафениба (ингибитора тирозинкиназ), сунитиниба и иматиниба показали снижение количества T-reg (при раке простаты, колореклальном раке), что коррелировало с общей выживаемостью [61]. Данные исследования представляются перспективными в отношении УР.…”
Section: таргетная терапия и исследования на уровне клеток клеточныхunclassified
“…Pierwsze próby wdrożenia tej metody polegały na nieswoistej stymulacji układu immunologicznego przez adiuwanty odpowiedzi immunologicznej oraz cytokiny (takie jak np. interleukina 2, interferon-alfa, czynnik martwicy guza alfa), dopiero później zaczęto wykorzystywać swoiste antygeny nowotworowe lub ich syntetyczne odpowiedniki, które miały stymulować endogenną odpowiedź obronną, głównie na drodze pobudzenia cytotoksycznych limfocytów T [30]. Preparaty zawierające te substancje są najczęściej podawane miejscowo, jako szczepionki doguzowe.…”
Section: Immunoterapia Onkologicznaunclassified